Obtención de ingredientes alimenticios con capacidad antioxidante mejorada por aplicación de distintos procesos a semillas de quinoa (Chenopodium quinoa) - Carciochi, Ramiro Ariel (2015)
The objective of this study was to obtain raw materials with enhanced antioxidant compounds through the application of different technological processes from quinoa seeds in order to be applied for the formulation of novel food products with potential functional properties.\nFirstly, the operational extraction conditions for phenolic compounds extraction from quinoa seeds were evaluated and optimized with the aim to obtain an extract rich in antioxidant substances. Thereafter, different processes such as germination, heat treatment, UV-C irradiation and combinations of these processes (germination + heat treatment and germination + UV-C irradiation) were evaluated as means to enhance the antioxidant capacity of seeds, selecting the optimal experimental conditions in each case. Contributions of different compounds such as phenolic acids, flavonoids, ascorbic acid, tocopherols and products of the Maillard reaction on the overall antioxidant capacity in case were evaluated. The ingredient that reached the maximum level of antioxidant activity was incorporated in the formulation of a gluten-free baked product, which it was subsequently evaluated by proximate composition, antioxidant capacity and overall acceptability.